Anodizing Pb Electrode for Synthesis of β-PbO2 Nanoparticles: Optimization of Electrochemical Parameters. Issue 13 (1st January 2019) - Hakimi, F.; Rashchi, F.; Dolati, A.; Astaraei, F. Razi
Abstract : Lead dioxide (PbO2 ) nanoparticles are electrodeposited on lead anode, using pulsed and constant direct current (DC) in 4.8 M H2 SO4 solution, to improve active surface area and promote catalytic activity of lead electrode. To increase the yield of PbO2 nanoparticles, current density, temperature and time of anodization are optimized using the response surface methodology. The optimum condition is found to be 25 mA cm −2 current density, 100°C temperature and 4-hour pulsed DC and 1-hour constant current for anodizing time. To increase the yield of nano β-PbO2 from 41.62% to 99%, porosity of the lead layer is increased and the passive layer of lead sulfate is broken. For this purpose, the lead substrate is pretreated in an electrochemical bath of sulfuric acid and perchloric acid, followed by immersing the electrode in hydrofluoric and nitric acid. Formation mechanism of β-PbO2 is also identified.